The Effect of Auditor Report Lag on Financial Performance and Company Governance in Consumer Cyclical Sector Companies - Dewi Susilowati; Salsabila Hana Saseka (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the effect of financial performance and corporate governance on audit report lag. Despite OJK No. 14/POJK/04/2022 regulation mandating that listed companies submit audited financial statements within 90 days of the fiscal year-end, many firms fail to meet this deadline. This study focuses on the consumer cyclicals sector, which shows the highest incidence of delay during the 2019–2022. The main research question is: Do financial performance and corporate governance significantly influence audit report lag in Indonesian consumer cyclical companies? While prior research has examined audit report lag in general, few studies focus specifically on the consumer cyclicals sector in Indonesia, especially during a period of macroeconomic fluctuation such as 2019–2022. This paper provides a fresh perspective by incorporating underexplored governance indicators like audit committee meeting intensity and board composition. This quantitative study uses purposive sampling, resulting in an unbalanced panel of 123 companies and 405 observations. Data were analyzed using EViews 13 with panel data regression. The analysis includes descriptive statistics, panel model selection tests, classical assumption tests, and hypothesis testing. Profitability (ROA), solvency (DAR), and the composition of the board of directors’ educational background negatively affect audit report lag. In contrast, the proportion of independent commissioners and the intensity of audit committee meetings have no significant effect. Financial performance and specific aspects of corporate governance can reduce audit report lag, which implies that companies and auditors can manage reporting timeliness more effectively by enhancing these factors. These findings can inform regulators and stakeholders to reassess existing policies.